Muzio Clementi - Jacquinot, Louise Françoise (engraver):::Creator::::::::::::; Hardy, Thomas, 1757-1805 (artist):::Contributor:::::::::::: (Wolfenbüttel; Germany; L. Holle)
Engraving of Muzio Clementi by Jacquinot based on the painting by Thomas Hardy.